(untitled) (Research, Society and Development, 2022)
The development of teaching skills are worked on teacher training courses, a space of permanent articulation between teaching, research and extension. In this context, there is the understanding that it is up to the teacher training courses to develop skills specific to the teaching profession to succeed in the teaching process learning. As teaching actions are diverse, it is significant to know the skills developed by teachers for the teaching of Science and Biology in Youth and Adult Education (EJA). Thus, we chose to conduct a case study of a qualitativa approach, which had as subjects professors of the EJA, who collaborated with the research allowing the attentive observation of its action and registration of information in an observation form, previously elaborated and theoretically based on carvalho’s text (1989), where the necessary skills for the development of a teaching practice that meets the socio-educational demands are presented. The analysis of the collected sources occurred in an interpretative way, presenting the ability to "look at students", "reinforcement" and "question", as well worked by the teachers of the EJA and the skills of "introduction", "variation" and illustrate with examples, as skills that need to be further explored/worked. It is important to highlight that the study does not present conclusive or static data, but information regarding a brief period of observation of the teaching activity. Path to reflections on the teaching of Science and Biology, teaching practices and teacher training.